2012
DOI: 10.1002/jmor.20045
|View full text |Cite
|
Sign up to set email alerts
|

Challenging limits: Ultrastructure and size‐related functional constraints of the compound eye of Stigmella microtheriella (Lepidoptera: Nepticulidae)

Abstract: With a body length of only 2 mm, the nepticulid Stigmella microtheriella (Stainton, 1854) is one of the smallest moths known to date. We investigated the optical design of its lemon-shaped compound eyes, which measure 83.60 μm in anterior-posterior and 119.77 μm in dorso-ventral direction. The eyes consist of about 123 facets, each of the latter just 9.9 μm in diameter. Transmission electron microscopy reveals an optical design with features intermediate between apposition and superposition optics similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…There exist effective mechanisms to enhance the sensitivity of very small compound eyes by adapting the functional morphology of the rhabdomers, as has been described by Paulus (1979) and Fischer et al (2011Fischer et al ( , 2012. Irrespective of whether or not eight cells represent the plesiomorphic condition early in the Cambrian the probably smaller number of receptor cells seen in our material and in the generally more benthic rather than pelagic recent isopods and amphipods requires an explanation.…”
Section: Photic Environment and Sensitivitysupporting
confidence: 58%
“…There exist effective mechanisms to enhance the sensitivity of very small compound eyes by adapting the functional morphology of the rhabdomers, as has been described by Paulus (1979) and Fischer et al (2011Fischer et al ( , 2012. Irrespective of whether or not eight cells represent the plesiomorphic condition early in the Cambrian the probably smaller number of receptor cells seen in our material and in the generally more benthic rather than pelagic recent isopods and amphipods requires an explanation.…”
Section: Photic Environment and Sensitivitysupporting
confidence: 58%
“…). Similar “atypical” superposition eyes have been mentioned by Ehnbohm () and Tuurala () for different groups of ditrysian moths and it has been also recently described in detail for the nepticulid Ectoedemia argyropeza (Honkanen and Meyer‐Rochow, ) and Stigmella microtheriella (Fischer et al, ) as well as several Gracillariidae (Fischer et al , 2013). See Fischer et al () for a detailed description of this type of eye now termed “intermediate.”…”
Section: Discussionsupporting
confidence: 76%
“…Investigations that involved tiny moths revealed the same trend (Honkanen & Meyer‐Rochow, ) and, moreover, showed that the species with reduced or abandoned clear‐zones had changed from the moth‐typical nocturnal lifestyle to the more diurnal one of a butterfly (Fischer et al ., , ). An additional approach to investigate body size‐related modifications to the clear‐zone of superposition eyes was used by Lau & Meyer‐Rochow (), who studied the microanatomy of the eyes of male and female Rhagophthalmus ohbai fireflies.…”
Section: Compound Eye Research Suggestionsmentioning
confidence: 99%
“…The more neutral term “intermediate eye type” was introduced by Fischer et al . () to stress that superposition (referring to the optical mechanism) was not likely to be effective in the small eyes and that without proper ontogenetic data of the eyes in question it was furthermore impossible to conclude in every case as to whether a small intermediate type of eye had evolved out of the superposition eye type or did have an apposition origin.…”
Section: Compound Eye Research Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation